2022
DOI: 10.2478/manment-2019-0091
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and Quality Assurance in Higher Education

Abstract: Internationalization is an inevitable phenomenon among all contemporary higher education institutions (HEIs) in a globalizing world. It is the driving force for development and progress. In course of the last 30 years, it became an inevitable element of HE management. However, it carries along a number of risks, pitfalls, and organizational challenges. To hedge those, quality assurance (QA) is called to the stage. HEIs therefore need not only to search for chances but also to increase the advancement of method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The concept of “value for money” holds institutions accountable by measuring return on investment. Conversely, the “fitness for purpose” and “transformative” viewpoints reflect an egalitarian approach, which focuses on meeting predetermined standards and emphasizes continuous improvement by increasing customer satisfaction and loyalty (Wysocka et al , 2022).…”
Section: Review Of Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of “value for money” holds institutions accountable by measuring return on investment. Conversely, the “fitness for purpose” and “transformative” viewpoints reflect an egalitarian approach, which focuses on meeting predetermined standards and emphasizes continuous improvement by increasing customer satisfaction and loyalty (Wysocka et al , 2022).…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…QA is another widely recognized quality concept, believed to have been introduced to HE from the corporate world in the 1980s, but lacks a universally agreed definition in the literature. One definition describes QA as “the processes of evaluating (assessing and monitoring), maintaining, guaranteeing, and improving the quality of the HE system, institution, or program” (Wysocka et al , 2022). QA can be further divided into internal QA (a developmental approach) that focuses on improving the quality of academic programs internally and external QA (a regulatory approach) that ensures quality at the institutional and programmatic levels (Dill, 2010).…”
Section: Review Of Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the rapid growth in students' international mobility, empirical research on the relationship between the IQA and the quality of higher education is scarce. However, some studies have found positive associations between them (Aleksandrova et al ., 2019; Fayda-Kinik, 2020; Wysocka et al ., 2022). Shan (2010) found a positive relationship between administrators' opinions of their universities' quality management and implementation of IQA standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, quality assurance aiming to ensure educational quality is a prominent focus of national higher education policies. For improving quality, higher education institutions need to develop international standards that respond to globalization and support international higher education; moreover, those standards should attract higher education institutions to adhere to internationalization of quality assurance (IQA) norms and guidelines (Bernhard, 2012; Wysocka et al ., 2022). The importance of quality assurance in higher education should extend beyond national interests to embrace IQA standards.…”
Section: Introductionmentioning
confidence: 99%